Leaf rust resistance in selections from barley landraces collected in Sardinia. - Czembor, Jerzy H.; Czembor, Henryk J.; Attene, Giovanna; Papa, Roberto (Plant Breeding and Seed Science, 2007)
Leaf rust caused by fungus Puccinia hordei has economic importance in many barley growing regions. Breeders are constantly looking for new effective sources of resistance to this pathogen. Landraces were proven to be rich source of resistance genes for resistance to major pathogens of barley. A total of 240 lines selected from 12 populations of barley landraces collected in Sardinia were tested for leaf rust resistance...